Treatment of endoscopic ultrasound‐guided coil deployment for isolated gastric varices using 0.035‐inch hydrocoil: Experience of three cases - Kazunori Nagashima; Ken Kashima; Yasuhito Kunogi; Fumi Sakuma; Koh Fukushi; Akira Yamamiya; Yoko Abe; Keiichi Tominaga; Makoto Iijima; Kenichi Goda; Rafael Romero-Castro; Atsushi Irisawa (DEN Open)
Abstract Endoscopic ultrasound (EUS)‐guided coil deployment (EUS‐coiling) has been newly developed for treating isolated gastric varices (iGV). This report describes three cases of EUS‐coiling for iGV using a 0.035‐inch hydrocoil (Azur; Terumo Corp., Tokyo, Japan). When used for EUS‐coiling, this hydrocoil provides the following benefits: Its electrically detachable system allows pull back. It has smooth and dense deployment. Moreover, it has a strong blood‐flow blocking effect because of its long length and large diameter with internal swelling functions of the hydrogel. Technical success of coiling was achieved in all cases. After coiling, additional treatments such as cyanoacrylate and sclerosant injection were performed as deemed appropriate. All iGVs were obliterated successfully. No adverse event occurred during the procedure or during the mean follow‐up of six months. Our findings indicate that this 0.035‐inch hydrocoil can be used to treat iGV safely and effectively.